Clinical Parameters and Outcomes in Periorbital Necrotizing Fasciitis. Issue 6 (November 2015) - Wladis, Edward J.; Levin, Flora; Shinder, Roman
Abstract : Purpose: To describe the clinical features associated with periorbital necrotizing fasciitis and to correlate these features with clinical outcomes. Methods: The case logs of 3 surgeons were used to identify cases of necrotizing fasciitis. Chart reviews were performed to characterize clinical metrics, and statistical analyses were performed. Results: Seventeen patients (9 males, 8 females; mean age = 48.1 years, standard deviation = 22.6 years) were identified with periorbital necrotizing fasciitis. Of these patients, 52.9% did not have immunodeficiencies, and 52.9% did not have antecedent trauma or infected facial lesions. One patient died from necrotizing fasciitis. A history of immunosuppression correlated with the requirement for exenteration, but did not correlate visual acuity of worse than 20/40 upon discharge from the hospital. Most of the patients (68.75%) were discharged with visual acuity of better than 20/40 in the affected eye. Conclusions: This study represents the largest case series of patients with periorbital necrotizing fasciitis. Most of the patients in this series did not have immunodeficiencies, and the majority were discharged with favorable visual acuities. Nonetheless, a history of immunosuppression correlated with the need for exenteration, but was not statistically linked with worse visual outcomes. Abstract : While periorbital necrotizing fasciitis is a potentially devastating entity, most patients that have this disorder retain useful visual acuity and most do not have preexisting immunosuppressive disease or antecedent trauma or lesions.